A REPORT ON TERTIARY STUDENTS’ SPEAKING ABILITY: A CASE STUDY OF ENGLISH SKILL RELATED TO SPECIFIC COGNITIVE STYLES - Fauzi, Rachmi Hasan (Universitas Muhammadiyah Tangerang, 2023)
This study aims to contribute theoretically and practically to the improvement of EFL teaching and learning process. Speaking learning techniques discussed in this research are role play and group discussion. The reason for researcher to use both techniques because both of them expose students to communicate one another so that they are expected to be confident to express their ideas. While the cognitive styles used in this researh as parts of learning style are field dependence and field independence. This research is done to show that besides preparing teaching materials and activities, teachers need to consider the students’ psychological part so that they can help their students optimally. Role play as well as group discussion give significant impact on the students’ speaking ability improvement.